Photoelectrochemical Performance and Charge Transport Kinetics of CuO Nanocone Arrays. Issue 2 (9th January 2020) - Wu, Fan; Zhang, Zhu; Jiang, Lan; Pathak, Rajesh; Xu, Haibin; Zhang, Tiansheng; Li, Xiaoyi; Jian, Ronghua; Qiao, Qiquan
Abstract : CuO nanocone arrays were grown in situ on an FTO substrate with thicknesses of 70–600 nm via a low-temperature hydrothermal synthesis method. Their morphological, optical, photoelectrochemical, and photocatalytic performances, were studied, as well as their charge transport photoelectric conversion kinetics. The photocurrent and photocatalytic degradation rate of CuO nanocone arrays increased when the nanocone length increased from 70 to 250 nm, and continued to decrease thereafter. Electrochemical impedance spectroscopy (EIS) indicated that charge separation and transfer were improved with a higher CuO/electrolyte interface area and longer CuO nanocones. But recombination also gradually increased with an increasing CuO nanocone length. Intensity-modulated photocurrent spectroscopy (IMPS) and intensity-modulated photovoltage spectroscopy (IMVS) spectra showed an increased transport time constant τ IMPS with a thicker CuO array, suggesting a more difficult hole transfer with a longer transport path. In contrast, a lower recombination time constant τ IMVS was observed in thicker CuO arrays, implying a more severe charge recombination, meaning that electron and hole recombination was inhibited in longer nanocones. Moreover, hole transport kinetics indicated that the low hole diffusion length was less than 50 nm, and was the likely cause of the limited photoelectric conversion in CuO nanocone arrays.